2005
DOI: 10.1111/j.1365-2672.2005.02718.x
|View full text |Cite
|
Sign up to set email alerts
|

Cheddar cheese cooking temperature induces differential lactococcal cell permeabilization and autolytic responses as detected by flow cytometry: implications for intracellular enzyme accessibility

Abstract: Aims: To determine the influence of cheese cooking temperature on autolysis and permeabilization of two lactococcal starter strains in broth and in Cheddar cheese juice during ripening. Methods and Results: Flow cytometry (FCM) was used to identify and enumerate intact and permeabilized cells in broth and in Cheddar cheese juice. Levels of intracellular enzyme activities were quantified concurrently. Permeabilized cell numbers increased for both strains in broth following a temperature shift from 32 to 38°C an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 28 publications
(88 reference statements)
4
46
0
Order By: Relevance
“…FCM has previously been employed to study the physiology of microbes in a variety of foodstuffs including milk (Gunasekera, Veal, & Attfield, 2003;Holm, Mathiasen, & Jespersen, 2004), drinking water (Pianetti et al, 2005), cheese (Sheehan, O'Loughlin, O'Cuinn, FitzGerald, & Wilkinson, 2005) and ground beef (Tortorello, Stewart, & Raybourne, 1998). Previously, the authors reported the use of FCM to demonstrate a heterogenous response by B. cereus endospores to simulated cooking regimes and refrigerated storage (Cronin & Wilkinson, 2008a data and provided a deeper insight into the physiological status of populations of B. cereus stored at various temperatures over the course of the 6 days incubation.…”
Section: Discussionmentioning
confidence: 97%
“…FCM has previously been employed to study the physiology of microbes in a variety of foodstuffs including milk (Gunasekera, Veal, & Attfield, 2003;Holm, Mathiasen, & Jespersen, 2004), drinking water (Pianetti et al, 2005), cheese (Sheehan, O'Loughlin, O'Cuinn, FitzGerald, & Wilkinson, 2005) and ground beef (Tortorello, Stewart, & Raybourne, 1998). Previously, the authors reported the use of FCM to demonstrate a heterogenous response by B. cereus endospores to simulated cooking regimes and refrigerated storage (Cronin & Wilkinson, 2008a data and provided a deeper insight into the physiological status of populations of B. cereus stored at various temperatures over the course of the 6 days incubation.…”
Section: Discussionmentioning
confidence: 97%
“…However, in many of the published studies few direct comparisons have been carried out between data obtained by FCM enumeration and that obtained by traditional plate counting. Sheehan et al (2005) noted strain related differences in the evolution of live, dead and permeabilised starter LAB strains in Cheddar cheese during ripening. FCM methodology involved the use of a SYTO9/PI stain combination with comparison of data from gates previously generated using a number of control populations.…”
Section: Immuno-fcm and Bacterial Enumerationmentioning
confidence: 96%
“…This estimation of viability is based on the assumption that intact (PI negative) cells are always live/viable while PI positive cells are always dead/ damaged. However, most FCM profiles will yield a double positive population (PI and SYTO 9 positive) which may actually make up a very significant proportion of cells in sample e.g cheese during ripening (Sheehan et al, 2005;Yanachkina et al, 2016). The latter cells may have differing metabolic activities and may well reflect a VBNC state.…”
Section: Stains and Viabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…FCM has been proven useful for measuring the lysis of cheese bacteria. Using the LIVE/DEAD BacLight bacterial viability kit, the lysis of Lactococcus lactis was monitored by counting the number of intact and permeable cells at diVerent time points [20,79]. FCM showed the presence of permeabilized cells at day 1 of cheese ripening.…”
Section: Startersmentioning
confidence: 99%